Keterlibatan Orang Tua dalam Perawatan Anak terhadap Stres dan Kecemasan Orang Tua di Ruang Intensif - Desi Anggraini; Nani Nurhaeni; Dessie Wanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to evaluate the results of research that has been published regarding the effect of parental involvement in child care on parental stress and anxiety in the intensive care unit. The method used is a systematic review through search strategies on eight electronic databases with the keywords used (Parent involvement OR Parent participation OR Family Integrity Care OR Family Centered Care) AND (pediatric intensive care OR PICU OR NICU) AND (Parent Stress OR Parent anxiety). The search results obtained 12 articles that would be assessed for quality with the guidance of the Joanna Briggs Institute (JBI). Research results show that parental involvement in child care in intensive care can reduce parental stress and anxiety. The highest significance was seen in the Family Integrated Care (FICare) program (p < 0.00043) and Family Centered Care (FCC) (p < 0.001) in the NICU room. In conclusion, all forms of parental involvement can reduce stress and anxiety, but parental involvement in child care in the PICU room is still limited. Keywords: Anxiety, Engagement, Intensive Room, Stress